Protective Mucosal Immunity to Ocular Herpes Simplex Virus Type 1 Infection in Mice by Using Escherichia coli Heat-Labile Enterotoxin B Subunit as an Adjuvant - Richards, C. M. (American Society for Microbiology, 2001)
The potential of nontoxic recombinant B subunits of cholera toxin (rCtxB) and its close relative Escherichia coli heat-labile enterotoxin (rEtxB) to act as mucosal adjuvants for intranasal immunization with herpes simplex virus type 1 (HSV-1) glycoproteins was assessed. Doses of 10 μg of rEtxB or above with 10 μg of HSV-1 glycoproteins elicited high serum and mucosal anti-HSV-1 titers comparable with that obtained using CtxB (10 μg) with a trace (0.5 μg) of whole toxin (Ctx-CtxB). By contrast, doses of rCtxB up to 100 μg elicited only meager anti-HSV-1 responses. As for Ctx-CtxB, rEtxB resulted in a Th2-biased immune response with high immunoglobulin G1 (IgG1)/IgG2a antibody ratios and production of interleukin 4 (IL-4) and IL-10 as well as gamma interferon by proliferating T cells. The protective efficacy of the immune response induced using rEtxB as an adjuvant was assessed following ocular challenge of immunized and mock-immunized mice. Epithelial disease was observed in both groups, but the immunized mice recovered by day 6 whereas mock-immunized mice developed more severe corneal disease leading to stromal keratitis. In addition, a significant reduction in the incidence of lid disease and zosteriform spread was observed in immunized animals and there was no encephalitis compared with 95% encephalitis in mock-immunized mice. The potential of such mucosal adjuvants for use in human vaccines against pathogens such as HSV-1 is discussed.